The Role of Central Banks in Modern Monetary Policy: A Review - Yani, Tri Apri (Advances: Jurnal Ekonomi & Bisnis, 2024)
Purpose: This paper aims to review and analyze the role of central banks in modern monetary policy. It seeks to provide a comprehensive understanding of the functions, objectives, and tools employed by central banks in the implementation of monetary policy. Study design/methodology/approach: A systematic literature review was conducted to gather relevant scholarly articles, books, and reports on the topic. The study design involved careful selection and analysis of the collected literature to identify key themes and insights related to the role of central banks in modern monetary policy. Findings: The review found that central banks play a crucial role in the formulation and execution of monetary policy. Their primary objectives typically include managing inflation, maintaining price stability, and promoting economic growth. Central banks employ various tools, such as interest rate adjustments, open market operations, and reserve requirements, to influence money supply and interest rates. Additionally, the study revealed that central banks act as lenders of last resort during financial crises, ensuring the stability and smooth functioning of financial systems. Originality/value: This review contributes to the existing body of knowledge by consolidating and summarizing literature on the role of central banks in modern monetary policy. It provides a comprehensive overview of the functions and tools employed by central banks, thereby enhancing the understanding of their significance in economic stability and growth. The findings of this study can be valuable to policymakers, researchers, and practitioners in the field of economics and finance.